Hereditary leiomyomatosis and renal cell cancer (HLRCC): renal cancer risk, surveillance and treatment. - Menko, F; Maher, E; Schmidt, L; Middelton, L; Aittomäki, K; Tomlinson, I; Richard, S; Linehan, WM (2014)
Hereditary leiomyomatosis and renal cell cancer (HLRCC) is an autosomal dominant condition in which susceptible individuals are at risk for the development of cutaneous leiomyomas, early onset multiple uterine leiomyomas and an aggressive form of type 2 papillary renal cell cancer. HLRCC is caused by germline mutations in the fumarate hydratase (FH) gene which inactivate the enzyme and alters the function of the tricarboxylic acid (Krebs) cycle. Issues surrounding surveillance and treatment for HLRCC-associated renal cell cancer were considered as part of a recent international symposium on HLRCC. The management protocol proposed in this article is based on a literature review and a consensus meeting. The lifetime renal cancer risk for FH mutation carriers is estimated to be 15 %. In view of the potential for early onset of RCC in HLRCC, periodic renal imaging and, when available, predictive testing for a FH mutation is recommended from 8 to 10 years of age. However, the small risk of renal cell cancer in the 10-20 years age range and the potential drawbacks of screening should be carefully discussed on an individual basis. Surveillance preferably consists of annual abdominal MRI. Treatment of renal tumours should be prompt and generally consist of wide-margin surgical excision and consideration of retroperitoneal lymph node dissection. The choice for systemic treatment in metastatic disease should, if possible, be part of a clinical trial. Screening procedures in HLRCC families should preferably be evaluated in large cohorts of families.